PELAYANAN PEMERINTAH KOTA DEPOK DALAM MENERBITKAN IZIN MENDIRIKAN BANGUNAN (IMB) TAHUN 2012-2014 - Surahman Surahman (KENEGARAAN, 2016)
Service function in the governance of an area is an absolute must to empower the community, it is becoming an important key in managing good governance (goodgovernance) with the basic principles of effective, efficient, transparent and accountable, would be the basis for taking a policy community development, local governments shouldbe able to involve the public directly from the planning, management and supervision, the public wrapped facilitate the attainment of the objectives of decentralization itself. Theresearch proves that government services Depok in issuing IMB residence on Investment Board and Licensing Services (BPMP2T) not running optimally, the indicator communityspirit to make the IMB is still very low, there are still many obstacles in the process of implementation and the persistence of rogue officers take the opportunity to receive a reward of making pictures of the building / process IPR misunderstanding in this case because the community and the community's own desire to be completed more quickly. Hospitality, care and concern public service workers is becoming very important to note.Attendant care and concern that can be proved with a firm stand indiscriminately or notselective to the rules that apply in this case is the maintenance of IMB in BPMP2T Depok. In addition, the chain of bureaucracy that must be passed by the community in the management of IMB extremely consume energy and time. With these conditions, then according to the authors of these factors also contribute less orderly IMB services at the field level. Keywords: IMB